1992
DOI: 10.1159/000182398
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Neonatal Screening for Congenital Adrenal Hyperplasia

Abstract: Without a neonatal screening programme for congenital adrenal hyperplasia (CAH), even in a country with a high level of medical assistance and sophisticated neonatal and endocrinological services, some patients affected by CAH may have died at birth or may remain undiagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
2
1
2
Order By: Relevance
“…From this survey we learned that the incidence of 2 1-OH deficiency in Israel was 1:20,987 live births. This incidence is lower than in many other coun tries [6]. We found that the incidence of 2 1-OH deficiency in the Arab population is more than 3 times higher than in the Jewish population (probably because of consangui neous marriages) and that in northern Israel it is as high as 1:5,080 live Arab births.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…From this survey we learned that the incidence of 2 1-OH deficiency in Israel was 1:20,987 live births. This incidence is lower than in many other coun tries [6]. We found that the incidence of 2 1-OH deficiency in the Arab population is more than 3 times higher than in the Jewish population (probably because of consangui neous marriages) and that in northern Israel it is as high as 1:5,080 live Arab births.…”
Section: Discussioncontrasting
confidence: 50%
“…The development of a 17-OHP assay from a filter paper-dried blood spot has facilitated neonatal screening of this dis ease [5]. Although such screening programs began 18 years ago, they are still not widespread [6]. This is because their cost-benefit value is still debatable.…”
Section: Introductionmentioning
confidence: 99%
“…(3), e posteriormente outros pesquisadores, descreveram uma técnica de ensaio para a dosagem da 17OH Progesterona (17OHP) a partir do sangue de recém-nascidos colhido em papel filtro (4)(5)(6)(7).…”
unclassified
“…Os resultados mostraram uma incidência de indivíduos com a forma perdedora de sal ainda maior que a esperada, passando de 1:490 para 1:282 após a triagem. Subseqüentemente, vários programas foram iniciados na Itália, Japão, França, Suécia, Suíça, Nova Zelândia e Israel, assim como em outros países onde a incidência da HAC-D21OH é muito elevada, como na Islândia (4)(5)(6)(7)(8). A triagem para HAC-D21OH foi introduzida nos EUA em 1987 e, atualmente, 38 estados norte-americanos realizam rotineiramente esta investigação (9).…”
unclassified
“…The incidence of carriers is approximately 1:55 [Cicognani, 1992;Pang et al, 1988]. In addition, the milder variant of CAH, nonclassical 21-hydroxylase deficiency, arises in about 1% of the general Caucasian population, making this variant one of the most frequent recessively inherited disorders in humans [Speiser et al, 1985], and an important cause of infertility in women [White et al, 1987].…”
Section: Discussionmentioning
confidence: 99%